Discovering Romans : content, interpretation, reception - Thiselton, Anthony C. (Discovering biblical texts., 2016)
This third volume in the Discovering Biblical Texts series offers readers a compact, up-to-date, and student-friendly introduction to Paul's letter to the Romans, focusing on its structure, content, theological concerns, key interpretive debates, and historical reception. Anthony C. Thiselton alerts readers to key issues and questions raised by the text, encouraging in-depth study and a sincere grappling with the theological and historical questions raised by this often-controversial epistle. He pays special attention to the book's reception and its influence on Christian history and culture, exploring and explaining the approaches and conclusions of a wide range of ancient and modern interpreters.